On-line marketingová komunikace - Tvarožková, Klára (Vysoké učení technické v Brně. Fakulta podnikatelská, 2021)
Bakalarska prace je zamerena na popsani marketingove komunikace vybrané firmy, dale take na navrhy zlepseni teto komunikace, jenz stoji na zpracovanych poznatcich z analyticke casti. Hlavnim cilem teto prace je navrhnuti vhodnych nastrojů teto komunikace, ktere povedou k naplneni sekundarniho cile teto prace. Tim je zvyseni povedomi o dane spolecnosti.

The bachelor’s thesis is focused on describing marketing communication of the chosen company, it also concerns suggestions to improve this communication, which is based on processing the knowledge from the analytical part. The main goal of this thesis is to design proper tools of this communication, which should lead to completing the secondary goal of this thesis which is raising awareness about the company.
On-line marketing communication
Keywords: On-line marketing; marketingova komunikace; PESTLE analyza; SWOT analyza; B2B marketing; marketingovy mix; komunikacni mix; socialni site; Online marketing; marketing communication; PESTLE analysis; SWOT analysis; B2B marketing; marketing mix; communication mix; social networks